The goal of the housing programme is to realize affordable or low cost housing construction for low income society, to improve access to basic services in urban and rural areas and promotion of local building materials. Waste material of rice straw is potential to be used as building materials becaue it contains fibres, SiD2 (if it is mixed with cement, it is possible to form calcium silicate hydrate), wax, pentosan, and lignin. This material is relatively cheap and easiZv available ill the imme - Abdul Rozak; Sri Mudiastuti; Aim Abdurachim Idris (PERTETA, 1998)
The goal of the housing programme is to realize affordable or low cost housing construction for low income society, to improve access to basic services in urban and rural areas and promotion of local building materials. Waste material of rice straw is potential to be used as building materials becaue it contains fibres, SiD2 (if it is mixed with cement, it is possible to form calcium silicate hydrate), wax, pentosan, and lignin. This material is relatively cheap and easiZv available ill the immediate vicinity. The addition of organic materials of the rice straw ill manufacturing panel board is intended to improve the panel quality such as strength, light weight, an thermal properties.